Lexical nonmanuals in German sign language empirical studies and theoretical implications - Meister, Nina-Kristin 1986- (Sign languages and deaf communities, 2020)
The book presents an empirical and theoretical investigation of lexical nonmanuals in German Sign Language including torso, head and facial expressions. Three empirical studies demonstrate the relevance of nonmanuals for the wellformedness of signs, their meaning, and lexical processing. Moreover, implications for the theoretical implementation of lexical nonmanuals concerning, e.g., articulation patterns and phonological status are discussed